Controllable synthesis of Zn/Cd(ii) coordination polymers: dual-emissive luminescent properties, and tailoring emission tendency under varying excitation energies. Issue 11 (12th February 2016) - Xing, Kai; Fan, Ruiqing; Gao, Song; Wang, Xinming; Du, Xi; Wang, Ping; Fang, Ru; Yang, Yulin
Abstract : With the help of rationally selected N-donor ligands, different dimensional architectures1–5 have been synthesized and they display dual-emission properties. Abstract : Based on a new asymmetric semi-rigid V-shaped tricarboxylate ligand 3-(2′, 3′-dicarboxylphenoxy)benzoic acid (H3 dpob), a series of zinc/cadmium(ii ) coordination polymers, {[Cd(Hdpob)(H2 O)3 ]·H2 O} n (1 ), [Cd(Hdpob)(bib)] n (2 ), [Zn(Hdpob)(bib)0.5 ] n (3 ), {[Cd1.5 (dpob)(2, 2′-bipy)]·0.5H2 O}2 n (4 ) and {[Cd3 (dpob)2 (4, 4′-bipy)2 ]·3H2 O} n (5 ) [bib = 1, 4-bis(1-imidazolyl)benzene; 2, 2′-bipy = 2, 2′-bipyridine; 4, 4′-bipy = 4, 4′-bipyridine], have been successfully synthesized via hydro(solvo)thermal reactions.1 forms a three dimensional (3D) supramolecular structure linked by two types of intermolecular hydrogen bonds based on zig-zag 1D chains, whereas2 and3 are obtained with a similar 2D layer structure by the same ligands and further connected into a 3D structure through hydrogen bonds.4 displays a homochiral 2D structure though two achiral ligands 2, 2′-bipy and H3 dpob, which contains right-handed helical infinite chains.5 is a 3D structure containing 2D metal-pyridine layer motifs, which are further pillared by beaded dpob 3− ligands to complete the structure and form a 6-connectedpcu (primitive cubic) net. In DMSO solvent, 1–5 illustrate dual-emission properties but have different low-energy emission (LE) intensities relatively. Extraordinarily, the difference resulting from central metals between2 and3 makes the intensity of LE dramatically enhanced and quenched. In this regard, the luminescence of2 and3 can be tuned between blue and green regions by varying the excitation light, and the tuning tendency can be tailored with inverse directions. Comparing their tunable-sensitivity to energy quantitatively, the theoretical calculation displays that3 (4.29%) is little higher than2 (3.59%) in a relative lower excitation wavelength zone. Meanwhile, five coordination polymers show distinct luminescence thermochromism in the solid state. When the temperature decreases from 298 K to 77 K, the red-shift from blue/green to the pure yellow light region is highlighted. The fantastic and unique luminescence phenomenon not only brings an insight into the synthesis of dual-emissive materials, but helps us to understand the luminescence behavior deeply as well.